2013
DOI: 10.1016/j.athoracsur.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myocardial Contractility Is Depressed in the Borderzone After Posterolateral Myocardial Infarction

Abstract: Background Contractility in the borderzone (BZ) after antero-apical myocardial infarction (MI) is depressed. We tested the hypothesis that BZ contractility is also decreased after postero-lateral MI. Methods Five sheep underwent postero-lateral MI. Magnetic resonance imaging (MRI) was performed 2 weeks before and 16 weeks after MI, and left ventricular (LV) volume and regional strain were measured. Finite element (FE) models were constructed and the systolic material parameter, Tmax, was calculated in the BZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…We demonstrated that a linear variation in contractility within the BZ, when compared to a homogeneous BZ contractility, reduces the mean square errors between the measured and the predicted strain fields. This result was later confirmed by direct force measurements in skinned fiber preparations from infarcted sheep LVs [5,6]. This improved description of regional ventricular mechanics is critical for using patientspecific models to predict the efficacy of existing or novel surgical procedures or devices for treating ischemic cardiomyopathy [7,8].…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…We demonstrated that a linear variation in contractility within the BZ, when compared to a homogeneous BZ contractility, reduces the mean square errors between the measured and the predicted strain fields. This result was later confirmed by direct force measurements in skinned fiber preparations from infarcted sheep LVs [5,6]. This improved description of regional ventricular mechanics is critical for using patientspecific models to predict the efficacy of existing or novel surgical procedures or devices for treating ischemic cardiomyopathy [7,8].…”
Section: Introductionmentioning
confidence: 54%
“…In Ref. [6], BZ T max was significantly reduced for all samples (18.9%, p ¼ 0.0067); moreover, myocyte cross-sectional area increased by 61% (p ¼ 0.021) in the BZ, but there was no increase in fibrosis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Following a myocardial infarction (MI), scar tissue gradually replaces myocardium that is lost through a process of collagen deposition and an increase in tensile strength of the tissue [2]. Borderzone myocardium becomes hypocontractile, leading to left ventricular dilation, increased left ventricle (LV) wall stress, and a decrease in ejection fraction [3]. LV dilation perpetuates infarct expansion, adverse ventricular remodeling, and dysfunction, which ultimately leads to heart failure.…”
Section: Introductionmentioning
confidence: 99%